Low grade gliomas treated at the University of Cape Town Academic Hospital complex: 2001-2017 - Kahl, Gisela (Department of Paediatrics and Child Health, 2021)
Background: The majority of central nervous system tumours in children are low grade gliomas (LGG). Long-term survival rates are high with a slow, progressive course. Tumour location and extent of resection affect outcome. Adjuvant therapy has an important role. Rationale: This study evaluated the demographic data of our patient population, the characteristics of LGGs in our setting, the time to presentation, and the role of adjuvant therapy including more targeted, novel biologic therapy such as BRAF/MEK inhibitors. The outcome of children with LGGs in our institution was assessed. Methods: A retrospective analysis was performed on all children < 15 years of age diagnosed with a LGG at Red Cross War Memorial Children's Hospital (RCWMCH) between 2001 and 2017. Data were collected from patient hospital folders, as well as paediatric oncology records and Groote Schuur Hospital radiotherapy records. Results: Eighty-six children aged 0.10-13.76 years (median 4.74 years) were diagnosed with LGGs between 2001 and 2017 at RCWMCH. Median time to presentation was 60 days. Sixtyfive patients (76%) were classified as having a WHO Grade I and 21 patients WHO Grade II (24%) tumours. Five patients (6%) had metastatic disease at presentation. The most common sites involved were the cerebellum (27%), hypothalamus (17%) and cerebrum (14%). The most common histology was juvenile pilocytic astrocytoma (JPA) (n=62; 73%). Gross total resection (GTR) was achieved in 21 patients (24%). Twenty-four patients (27%) received chemotherapy of which 11 patients progressed. Twenty-two patients received radiotherapy (26%), of which 3 patients progressed. The estimated 5-year overall survival (OS) was 86.8% and the estimated 5-year progression free survival (PFS) was 42.8%. The presence of a BRAFV600E mutation was checked in 4 patients since 2013, all had JPA histology, and all were negative. Discussion: Our patient demographic differed from published data with respect to younger age at presentation and female predominance. Time to presentation was relatively short. The majority of LGGs were cerebellar, with JPA histology being the most common. GTR was achieved in almost a quarter of patients. WHO Grade II histology did not significantly impact PFS and OS. Children < 3 years had a lower PFS compared to children > 3 years, but OS was similar. OS in this study was comparable to published data in developed countries, however PFS was slightly lower. Conclusion: Our outcomes are similar to those achieved in developed countries. Chemotherapy and radiotherapy are valuable adjuncts to treatment. The presence of a BRAF alterations should be tested in recurrent/progressive disease, to guide use of novel treatments.